Tinjauan Yuridis Perlindungan Hukumterhadap Korban Perdagangan Anak Di Indonesia - Ifahda Pratama Hapsari (Jurnal Justiciabelen, 2020)
The increasing number of cases of child trafficking shows that the level of crime or crime, especially in cases of trafficking in children, has an unstable number and cannot be suppressed at all in the past 6 (six years) 2005-2010). This has an impact on victims of trafficking, especially in children who experience prolonged stress, health problems, and infectious diseases caused by these children in per trade. Efforts to increase protection for victims of trafficking, especially in children, can conducted through supervision and control of the ways parents and families take care of their children through guidance and direction of religious lectures where parents and families have a big stake in protecting their own children.